Penilaian Potensi Reproduksi Induk Sapi di Kecamatan Amahai, Maluku Tengah - Kainama, Rio S; Siwa, Isak P; Tagueha, Astri (Jurnal Agrosilvopasture-Tech, 2023)
Reproductive potential should be routinely evaluated because it significantly impacts the farmer's economy and the cattle population in ruminant development areas. This study aims to assess the reproductive potential of cows in the Amahai sub-district, which is one of the development points for the industrial livestock area in Maluku Province. Purposive and random sampling methods selected 98 cows owned by 30 breeders from 3 villages. Cows were evaluated for their reproductive performance, whereas breeders' evaluation was focused on general characteristics and rearing systems, and the results were analyzed descriptively. The results showed that the potential reproductive value of cows in Amahai was generally considered promising because of the high percentage of calves born alive (97.98%), low rate of stillborn (1.13%), and abortion (1.1.7%), there was no history of dystocia. The population was dominated by cows with mediocre body condition scores (93.88%). Conversely, cows in this area have too young a first mating age (11.3 months), service per conception > 1 (2.65), and long days open (4.71 months). This reproductive potential will be maximized if breeders understand the mating season, recognize estrus signs, implement a short weaning period (≤ 2 months after parturition), and make reproductive records.